Euro-integration of the Republic of North Macedonia: Aligning with the EU acquis in Family related Matters and Children’s Rights, Iustinianus Primus Law Review Vol. 15, No. 1 - Ignovska Elena (Faculty of Law 'Iustinianus Primus' Skopje, 2024)
This paper explores the process of Euro-integration of the Republic of North Macedonia, focusing on the aligning of its legal framework with the European Union acquis (the accumulated body of EU legislation and regulations) in family-related matters and children’s rights. The Republic of North Macedonia's accession to the EU is a complex process, requiring alignment with various EU policies and regulations. This paper explores the national legal consistency in a rather sensitive field to be harmonized, outlining the challenges and opportunities that arise during this transformative journey. By evaluating the progress made thus far and identifying areas that require further attention, this study aims to contribute to the broader discourse on the North’ Macedonia’s European integration.
Keywords: Euro-integration, Republic of North Macedonia, EU acquis, family law, children’s rights